Typhus Fever: An Overlooked Diagnosis (Journal of Health, Population and Nutrition, 2009)
A case of typhus fever is presented. On admission, the clinical diagnosis was typhoid fever. Forty-eight hours after admission, the presence of subconjunctival haemorrhage, malena, and jaundice raised the possibility of a different aetiology, the two most likely differentials being dengue and typhus. Finally, a co-infection of typhoid and typhus was discovered. This uncommon clinical scenario should be taken into account in the management of patients with high fever on admission being treated as a case of typhoid fever. Key words: Co-infections; Morbidity; Typhoid; Typhus; Bangladesh doi: 10.3329/jhpn.v27i3.3385 J Health Popul Nutr 2009 Jun;27(3):419-421